The Relevance of Crossdressing Laws from the Perspective of Hadith and MUI Leaders of Malang City: Relevansi Hukum Crossdressing Perspektif Hadis dan Tokoh MUI Kota Malang - Ianatut Tazkiyah; Nasrulloh Nasrulloh (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
The rapid development of technology makes it easier for people to create profits to achieve profits. One of them is the phenomenon of crossdressing carried out by content creators on social media to entertain and get other benefits. Crossdressing is really considered to disturb order and comfort, because many people use it as a means of disguise or even to the point of completely changing their identity according to the clothes they wear. This study aims to determine the phenomenon of crossdressing caused by work in the study of hadith and opinions from MUI figures in Malang City. This type of research is descriptive qualitative, which is empirical in nature. The phenomenological approach is from the opinion of the MUI Kota Malang figure. The result of this study is that crossdressing laws are prohibited both according to sahih hadith, as well as the MUI of Malang city, because it includes tasyabbuh, and the opening of other job opportunities that do not violate religious rules.